A PROSPECTIVE STUDY OF EPIDEMIOLOGICAL FACTORS AND OUTCOME IN PATIENTS OF DIABETIC FOOT WOUND ATTENDING J.A. GROUP OF HOSPITALS: A TERTIARY CARE CENTRE - THAKRE, SANDEEP; DEHARIYA, CHANCHLESH; UPADHYAY, SHIVAM; NARGESH, SHAILENDRA SINGH; SINGH, MANISHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To study about epidemiological factors related to diabetic foot wound such as age, sex, duration of diabetes, relation to ongoing retinopathy, and nephropathy. Methods: After obtaining approval from ethical committee, the present study is to be conducted on 100 patients of diabetic foot in the Department of Surgery, JA Group of Hospitals and GR Medical College, Gwalior (MP) during January 2020 to June 2021 after getting written informed consent from the patients. Results: In our study, out of 100 cases, most of the diabetic foot wound cases observed were in the 50–59 years age group with a mean age of 52.23 and a standard deviation of ±14.92. Out of 100 cases, 82 (61.%) were male and 29 (38.66%) were female. Therefore, male: female ratio was 4.5:1. In our study of 100 patients, 70 (70%) presented with ulcer with or without necrotic patch, gangrene and 30 (30%) with cellulitis with or without abscess. Among all patients of diabetic foot, wound 62 (62%) were associated with retinopathy and 47 (47%) were associated with diabetic nephropathy. Conclusion: Diabetic foot wound is more common in men due to their increased susceptibility to trauma and occupation. Diabetic patients at risk for foot complication must be educated about risk factors and the importance of foot care, including the need for self-inspection and surveillance, monitoring, daily foot hygiene, use of proper footwear, good diabetes control, and prompt recognition and early standard treatment of newly discovered lesions.